An An Identification of Phrasal Verb in the Movie Entitled “Harry Potter and the Prisoner of Azkaban” - Zahra, Fitria (Jurnal Pendidikan Bahasa Inggris undiksha, 2023)
Language has a great effect as an important part of human life that is always used in the daily life by human being. It is important to teach and educate the students as ESL/EFL students about phrasal verbs in order to make them understand and capable in using phrasal verbs especially when they have interaction in English. This study aims to analyze the phrasal verbs, types and the meaning of phrasal verbs that are found in the movie entitled “Harry Potter and the Prisoner of Azkaban”. The instruments of this study are the researcher as the main instrument and a checklist that is used to collect the data. This study used documentation as the method of the data collection. The result of this study showed that there are 102 of phrasal verbs that were found in the movie. There were two types of phrasal verbs that were found in this study, such as transitive phrasal verb (separable phrasal verb and inseparable phrasal verb) and intransitive phrasal verb. Both of the types of the phrasal verbs were found in the movie of this study. Those are consisted of 74 of intransitive phrasal verb and 28 of transitive phrasal verb (14 of separable phrasal verb and 14 of inseparable phrasal verb).